Children as caregivers : the global fight against tuberculosis and HIV in Zambia - Hunleth, Jean, 1976- (Rutgers series in childhood studies., 2017)
Medical anthropologist Jean Hunleth chronicles the experiences of children living with parents and guardians who are suffering from these infectious diseases and shows how their perspectives matter in the global debates about health care. Children as Caregivers examines how well intentioned practitioners fail to realize how children take on active caregiving roles when their guardians become seriously ill. Using ethnographic methods, and listening to the voices of children as well as adults, Hunleth makes the caregiving work of children visible. Children actively seek to "get closer" to ill guardians by providing good care. Both children and ill adults define good care as children's attentiveness to adults' physical needs, their ability to carry out treatment and medication programs in the home, and above all, the need to maintain physical closeness and proximity.